Research report on the inclusion of a student diagnosed with the rare Dandy-Walker syndrome (Research, Society and Development, 2021)
Dandy Walker Syndrome is rare, characterized by malformations such as hydrocephalus, distancing of the cerebellar hemispheres, visual acuity problems, cognitive and intellectual delay, psychomotor alterations, among others. Little known and widespread in school spaces. This makes it difficult to include these students, who need collaborative support among school professionals. The student who has this syndrome needs psychomotor work and communication support. This work is an experience report on the inclusion of a student with malformations of the syndrome, for six years, who had been at three schools and who presented, in addition to severe learning difficulties, inappropriate social behaviors and difficulties to communicate in the expected manner for his chronological age, now 12 years old. The methodology used was bibliographic research and field work. It was noticed over these years that it developed gradually, and that this improvement began when the necessary school adjustments were punctual and directed, with the objective of expanding their proper behavioral conduct and knowledge of the world to work on their learning from this. and expected pedagogical behaviors for their chronological age.